2014
DOI: 10.2991/icmce-14.2014.149
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Frost Heaving Characteristics of Coarse Grained Soil Filler of High Speed Railway Subgrade in Cold Region

Abstract: The Haerbing-dalian high-speed railway subgrade packing is as the research object. Influence factors of frost damage are analyzed, such as packing soil(size composition,Mineral composition,compactness),moisture,temperature external load and salt content, etc. Through characteristic tests of frost heaving, research on Influence of subgrade frost heave with or without the condition of train load conditions was made, including content of fine grained soil, water-holding capacity, packing grading, permeability coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The effect of fines content on the dynamic parameters of GRS is closely related to its water content. When the soil is in the saturated state, the larger the fines contents, the smaller the dynamic shear modulus and the higher the damping ratio [61]. Figure 13 plots the evolution of dynamic parameters with the variation of fines contents of GRS.…”
Section: Characteristics Of Dynamic Parameters Of Grsmentioning
confidence: 99%
“…The effect of fines content on the dynamic parameters of GRS is closely related to its water content. When the soil is in the saturated state, the larger the fines contents, the smaller the dynamic shear modulus and the higher the damping ratio [61]. Figure 13 plots the evolution of dynamic parameters with the variation of fines contents of GRS.…”
Section: Characteristics Of Dynamic Parameters Of Grsmentioning
confidence: 99%
“…Tai et al (2017) (Tai et al, 2018) systematically studied the variation characteristics of the temperature and deformation fields of subgrade engineering of the Ha-Qi highspeed railway in the deep seasonal freezing soil zone. With a continuous understanding of the frost heave mechanism of frozen soil, some scholars began to study the influence of different factors on the frost heave of coarse-grained soil (Konrad, 2008;Du et al, 2014;she et al, 2019). Through laboratory tests, some scholars found that augments with fine particles and clay minerals would improve the frost susceptibility of coarse-grained soil (Vinson et al, 1986;Ye et al, 2007;Xu et al, 2011;Wang and Yue, 2013), and some scholars considered that water content, porosity, negative temperature, dry density, and compaction level affect the frost heave of subgrade (Nie et al, 2013;Wang et al, 2016;Luo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Permafrost area is about 22.3% territory area in China, ranking third in the world after Russia and Canada, while the total frozen soil area including seasonal frozen soil accounts for about 70% of the total area. Frozen soil has a great impact on construction of the road engineering, such as part typical long sections of Jilin province over the Changyu highway [1] along which severe lateral deflection occurred due to the winter frost heave and near the shoulder also generated obvious lateral deformation and collapse. The melting of seasonally frozen ground resulted in severe frost boiling of road surface in Baoquanling sections of the Haluo highway in Heilongjiang province.…”
Section: Introductionmentioning
confidence: 99%